2016
DOI: 10.1371/journal.pbio.1002409
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexpansion of RNA Bacteriophage Diversity

Abstract: Bacteriophage modulation of microbial populations impacts critical processes in ocean, soil, and animal ecosystems. However, the role of bacteriophages with RNA genomes (RNA bacteriophages) in these processes is poorly understood, in part because of the limited number of known RNA bacteriophage species. Here, we identify partial genome sequences of 122 RNA bacteriophage phylotypes that are highly divergent from each other and from previously described RNA bacteriophages. These novel RNA bacteriophage sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
114
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 47 publications
0
114
1
Order By: Relevance
“…Like these factors, lys M occupies no dedicated genetic space 5 , highlighting the ability of small phages to maximize their coding capacity. Recent analysis of publicly available metagenomes and transcriptomes has revealed that the ssRNA leviviruses are more ubiquitous and diverse than previously appreciated 17,18 , at least in part because of extensive use of RNase during virome sampling. RNA phages are therefore estimated to constitute a substantial fraction of the total virome in gut samples 19 , representing a deep resource of genomic ‘dark matter’.…”
mentioning
confidence: 99%
“…Like these factors, lys M occupies no dedicated genetic space 5 , highlighting the ability of small phages to maximize their coding capacity. Recent analysis of publicly available metagenomes and transcriptomes has revealed that the ssRNA leviviruses are more ubiquitous and diverse than previously appreciated 17,18 , at least in part because of extensive use of RNase during virome sampling. RNA phages are therefore estimated to constitute a substantial fraction of the total virome in gut samples 19 , representing a deep resource of genomic ‘dark matter’.…”
mentioning
confidence: 99%
“…Bacteriophages (phages) are estimated to be the most abundant organisms on earth, with key roles in shaping the composition of microbial ecology by lysing bacteria or transferring genes12. Despite the numerous available studies on DNA bacteriophages, the biology of RNA bacteriophages has been poorly investigated.…”
mentioning
confidence: 99%
“…Although some phage genes are similar and functionally conserved, the number of potential genes encoded by this many phages is incomprehensible. These worldwide estimates likely even underestimate the number of phages with either single-stranded RNA or double-stranded RNA genomes, or those that dominate unique environments, as these classes may not be identified by standard phage isolation and genomic sequencing approaches (92, 93), or are under-annotated because of their divergence from more well-characterized phage (94). One of the few characterized single-stranded RNA phage is the enterobacterial phage Qβ, whose study led to the discovery of Hfq (23).…”
Section: Vast Potential To Identify New Rna Binding Proteins Regulatmentioning
confidence: 99%